Biological monitoring of exposure to nerve agents - Bajgar, J (British journal of industrial medicine, 1992)
Changes in acetylcholinesterase activity in blood and some organs of rats after intoxication with sarin, soman, VX, and 2-dimethylaminoethyl-(dimethylamido)-phosphonofluoridate (GV), in doses of roughly 2 x LD50 given intramuscularly, were obtained from published data and by experiment. The time course of inhibition of acetylcholinesterase in blood, regions of brain, and diaphragm and the occurrence of signs and symptoms of poisoning (none, salivation, disturbed ventilation and fasciculations, convulsions, or death) were summarised and compared. When blood enzyme activities were 70-100% normal, no obvious signs were seen; at 60-70%, salivation occurred; at less than 30-55%, disturbed ventilation and fasciculations were seen, and at 15-30%, convulsions occurred. Less than 10% was fatal. In experiments with narcotised dogs, the blood acetylcholinesterase activity and the ability to reactivate it with trimedoxime were determined after intoxication by intramuscular administration of the four compounds. It is concluded that acetylcholinesterase activity in the blood corresponds to that in the target organs and can be considered as an appropriate parameter for biological monitoring of exposure to nerve gases. Moreover, determination of reactivation of blood acetylcholinesterase gives more information than simple determination of enzyme activity.
Keywords: Animals; Acetylcholinesterase; Organothiophosphorus Compounds; sarin; Seizures; organothiofosforové sloučeniny; bránice; Organophosphorus Compounds; Salivation; Sarin; organofosforové sloučeniny; Dogs; mozek; Soman; acetylcholinesterasa; Brain; Diaphragm; soman; krysa rodu Rattus; salivace; zvířata; Rats; psi; záchvaty